Investigation of the Relationship between Middle School Students’ Motivation and Attitudes toward Social Studies - Subasi, Yakup (Science Insights Education Frontiers, 2023)
The two most important affective skills that influence students’ success in a course are motivation and attitude. The desire to achieve a specific goal is related to motivation, while the experiences gained in the pursuit of that goal shape one’s attitude. The high motivation of students for a course is also an indicator of their positive attitudes toward that course. This study aims to determine the predictive power of 6th-grade middle school students’ attitudes toward the social studies course on their motivation to engage in this course. A correlational survey model was employed for this quantitative research. The participants in the study comprise 306 6th-grade middle school students enrolled in schools affiliated with the Republic of Türkiye Ministry of National Education during the 2022-2023 academic year. The “Social Studies Attitude Scale” and “Social Studies Motivation Scale” were used as data collection tools. The results of the multiple regression analysis revealed that the correlation between motivation and attitude varies depending on their dimensions. Moreover, it was observed that the predictive power of attitude on motivation differed across dimensions.